La visita del papa Benet XIII a València de 1414-1415: una aproximació a la seua memòria en la tradició historiogràfica valenciana. - SERVER, BLAI JOSEP SERVER (Scripta, 2017)
Pope Benedict XIII, Pero Martínez de Luna, visited the city of Valencia between December 1414 and July 1415. This paper examines the presence of the visit in the Valencian historiographical tradition. Specifically, it deals with the Valencian memoir works that, from the 15th century up to now, have paid attention to this event, in order to conclude that its memory was kept mainly in the circles of the ecclesiastical (especially in those related to the Cathedral of Valencia) and municipal power. Beyond these spheres, the Papal visit was progressively forgotten, even though the considerable impact that it must have had upon its contemporaries in the 15th century.